Locally advanced basal cell carcinoma: Real‐life data with sonidegib. Issue 6 (21st March 2022) - Toffoli, Ludovica; Conforti, Claudio; Zelin, Enrico; Vezzoni, Roberta; Agozzino, Marina; di Meo, Nicola; Zalaudek, Iris
Abstract: In recent years, the category of hedgehog pathway inhibitor (HHI) has shown great results in patients with advanced basal cell carcinoma (aBCC), but few real‐life data on efficacy and safety profile of sonidegib are available. We report our management of locally advanced BCCs (laBCCs) with sonidegib, also describing the favorable response of locally advanced basosquamous carcinomas (laBSCs) treated with this hedgehog signaling inhibitor. Sonidegib was generally well tolerated and it achieved high response rates, improving quality of life. Our single‐center experience could be useful to better delineate long‐term efficacy and tolerability profile demonstrated in the trials described in literature. Moreover, our cases provide preliminary evidence that sonidegib might be effective for laBSC.